ANALISIS PENYUSUNAN DOKUMEN TEMATIK EKONOMI MAKRO - Arzan Zamir; Ezar Faruq (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2023)
Based on the results of measuring PPH consumption for the City of Surakarta in 2020, the PPH score was 90.8 with a total energy consumption of 2,031 Kcal/capita/day. This figure illustrates that the Energy consumption of Surakarta City residents has reached 94.5% of the ideal Energy Adequacy Rate (AKE) of 2,150 Kcal/capita/day. Meanwhile, from the PPH Availability of Surakarta City, a score of 91.9 was obtained with a total energy availability of 2,481 Kcal/capita/day. Judging from these two figures, in terms of quantity and quality in general, the food consumption of Surakarta City residents is close to ideal, so it is expected that the status of the Surakarta City community as a whole is in good condition. Then from the availability side, an overview of the various food ingredients available in Surakarta City has reached 103% of the Availability Energy Adequacy Rate (AKE) of 2,310 Kcal/capita/day.